Types of knowledge and preferences for solving problems - Acevedo Borrego, Adolfo (2010)
The Knowledge, from the perspective of the Greeks, it has four types: Empeiria, tekhne, episteme and nous. These types have different characteristics, as they target the source dimension (facts and concepts), or the purpose dimension (contemplation or domain). On the basis of these dimensions is presented a tool kit to collect, develop and build personal strengths, arising from the disposition of knowledge itself. This tool allows to outline the productive potential of staff, from the perspective that the knowledge acquired, determines the disposition and development of ability to make decisions and solve problems. In the sample studied, it was noted that professionals have different susceptibility to the dimensions of knowledge, which leads to a different personal profi le for the resolution of problems. According to the predominant profi le, professionals are more focused on the analysis and study, and less problem solving and mastery orientation is low. In general, this study provides evidence to broaden the perspective of development and professional learning.